(3GdbWY hGdGSJFfGas - (3GdfMGS , CMeO Hf eMeO Hf ESeGYjd GdeQGOj GdeUQj, CHh LYaQ,J (B338 (3g` s ((3eMeO Hf ehSi Hf YeQGf s)
(3ChdgG (B:s
(3bd CHhLYaQ CMeO Hf eMeO GdfMhj(B: (3GdMeO ddg GdPj GaJJM HGdMeO cJGHg , LYd dCgd GdYde Phj GdYed KhGHg s
(3BNQgG (B:s
(3hMLJgG Cfg Udi Gddg Ydjg hSde CeQ Cf jbhd gPG cdg , hgcPG bd CYhP HQH Gdadb , h CYhP HQH GdfGS hGddg CYde s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B208 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B82s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs